A Review: Thermoelectric cooler application for portable beverage cooler - N Fuad; Azridjal Aziz; Rahmat Iman Mainil (Prosiding SNTTM, 2025)
Thermoelectric cooler (TEC) based on the Peltier effect offers a compact, silent, and environmentally friendly portable cooling solution. It can be used to preserve perishable food, medicine on remote area with limited or no electricity. This review explores experimental and theoretical findings from studies published between 2015 and 2025, with focus on portable beverage applications. Key material advances (average ZT ≈ 1–1.4) are traced, dominant thermal management bottlenecks are identified, and emerging optimization methods including artificial intelligence-assisted design are discussed. The system coefficients of performance (COPs) reported for one-stage beverage coolers have remained modest (0.2–0.9). However, recent prototypes have demonstrated the capability to achieve drink temperatures below 5 °C from 25 °C ambient within 30 minutes. These prototypes also show promising pathways for higher efficiency through hybrid photovoltaics, advanced heat sinks, and adaptive control.